A new species of the highly modified hypogean genus Giraffaphaenops Deuve, 2002 (Coleoptera: Carabidae: Trechinae) - Tian, Mingyi; Luo, Xiaozhu (Zootaxa, 2015)
Giraffaphaenops yangi n. sp. is described from a limestone cave named Shizikou Dadong, Tianlin County, northwestern Guangxi, China. It is the second species of this genus, which is the most morphologically modified in the tribe Trechini in terms of troglobiomorphy. So far, Giraffaphaenops ranges in a small karstic area in northwestern Guangxi. Of the two known species, G. clarkei Deuve, 2002 was recorded from four caves in Leye County, whereas G. yangi n. sp. is known from the only type locality cave in Tianlin County. A distributional map of the genus Giraffaphaenops is also provided. In addition, two females of G. clarkei are recorded from the cave Yanwu Dong, Leye County.